1999
DOI: 10.1128/aem.65.7.2954-2960.1999
|View full text |Cite
|
Sign up to set email alerts
|

Development of Primers to O-Antigen Biosynthesis Genes for Specific Detection of Escherichia coli O157 by PCR

Abstract: The chemical composition of each O-antigen subunit in gram-negative bacteria is a reflection of the unique DNA sequences within eachrfb operon. By characterizing DNA sequences contained with each rfb operon, a diagnostic serotype-specific probe toEscherichia coli O serotypes that are commonly associated with bacterial infections can be generated. Recently, from an E. coli O157:H7 cosmid library, O-antigen-positive cosmids were identified with O157-specific antisera. By using the cosmid DNAs as probes, several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 52 publications
0
47
0
2
Order By: Relevance
“…Sequence variation in the 3¢-end of the eae gene encoding intimin, which is part of the locus of enterocyte effacement (LEE), allowed PCR primers relatively specific for O26, O111 and O157 to be designed (Gannon et al 1993;Louie et al 1994Louie et al , 1998. Specific portions of the genetic loci encoding biosynthesis of the O-antigen were analysed to design PCR primers to detect specifically O104, O111, O113 and O157 serogroups (Desmarchelier et al 1998;Paton and Paton 1998b, 1999a, 1999bWang et al , 2001Maurer et al 1999). Until now, no specific test for O91 has been described, although several reports described the presence of E. coli O91 in patients with haemolytic uraemic syndrome (HUS).…”
Section: Introductionmentioning
confidence: 99%
“…Sequence variation in the 3¢-end of the eae gene encoding intimin, which is part of the locus of enterocyte effacement (LEE), allowed PCR primers relatively specific for O26, O111 and O157 to be designed (Gannon et al 1993;Louie et al 1994Louie et al , 1998. Specific portions of the genetic loci encoding biosynthesis of the O-antigen were analysed to design PCR primers to detect specifically O104, O111, O113 and O157 serogroups (Desmarchelier et al 1998;Paton and Paton 1998b, 1999a, 1999bWang et al , 2001Maurer et al 1999). Until now, no specific test for O91 has been described, although several reports described the presence of E. coli O91 in patients with haemolytic uraemic syndrome (HUS).…”
Section: Introductionmentioning
confidence: 99%
“…Using conventional methods, screening for E. coli serogroups depends on isolation of the bacteria, confirmation of E. coli and identification of the O-antigen using serotyping methods. However, as this approach is time consuming, several studies have proposed O-serotyping using PCR, by targeting specific portions of the genetic loci encoding biosynthesis of the O-antigen (Desmarchelier et al 1998;Paton 1998b, 1999a,b;Wang et al , 2001Wang et al , 2002Maurer et al 1999;D'Souza et al 2002;Perelle et al 2002bPerelle et al , 2004Fratamico et al 2003;DebRoy et al 2004;Guo et al 2004) or the LEE (Gannon et al 1993;Louie et al 1994Louie et al , 1998Oswald et al 2000;Sharma 2002;Perelle et al 2004). In a previous study, we reported the serotyping by 5¢-nuclease PCR of STEC strains based on the selection of primers and probes targeting the O-antigen gene clusters of E. coli O26, O55, O91, O111, O113, O157, the eae gene of E. coli O103, the O-island 29 of E. coli O145, and the flagellar H7 antigen gene (Perelle et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…PCR assays have been described for detecting STEC and identifying the genes involved in their virulence but it is important to rapidly determine the STEC serogroup in clinical cases to define a cluster of related cases and to investigate suspected food samples. Several O-serotyping PCR assays, based on the sequence variation in the locus of enterocyte effacement (LEE) (Gannon et al 1993;Louie et al 1994Louie et al , 1998Oswald et al 2000;Sharma 2002;Sharma and Dean-Nystrom 2003;Perelle et al 2004), in the genetic loci encoding biosynthesis of the O-antigen (Desmarchelier et al 1998;Paton 1998b, 1999a,b;Wang et al , 2001Wang et al , 2002Maurer et al 1999;D'Souza et al 2002;Perelle et al 2002bPerelle et al , 2004Fratamico et al 2003;DebRoy et al 2004;Feng et al 2004;Guo et al 2004), in the uidA gene (Cebula et al 1995;Yoshitomi et al 2003) or in the O-island 29 (Perelle et al 2002a(Perelle et al , 2003 have been proposed for the specific detection of serogroups O26, O55, O91, O103, O104, O111, O113, O114, O121, O145, O157 and O172. Sequence variation in the 3¢-end of the eae gene encoding intimin, which is part of the LEE allowed PCR primers relatively specific for O26, O103, O111 and O157 to be designed (Gannon et al 1993;Louie et al 1994Louie et al , 1998Oswald et al 2000;Sharma 2002;Perelle et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic characterization of SF O157, screening of 10 virulence genes, stx2 subtyping, and MLVA genotyping Molecular identification of SF O157 was carried out by a multiplex-PCR (M-PCR) detecting the genes rbf O157 (Maurer et al, 1999), fliC H7 (Lindstedt et al, unpublished), terE (Taylor et al, 2002) and the Shigella resistance locus (SRL) (Janka et al, 2005). The dinB gene (Lindstedt et al, unpublished) was used as an internal amplification control.…”
Section: Extraction Of Dnamentioning
confidence: 99%